Analisis Pelepasan Informasi Rekam Medis Kepada Pihak Ketiga di RSU Budi Rahayu Pekalongan Tahun 2022 - Yosephin Celinda; Natalia Kristiani; Rifki Rifki; Maulina Latifah (EMVIRO Jurnal Ilmiah Penelitian Kesehatan, 2025)
Providing medical information must follow applicable procedures. Medical information can be provided if the patient signs and authorizes a third party to obtain medical information about him. The aim of this research is to determine the procedure for releasing medical record information to third parties at RSU Budi Rahayu Pekalongan. This type of research uses qualitative descriptive research using observation and interview methods and the data source uses primary data, namely power that is directly given to the data collector. The results of the research show that the procedure for releasing medical record information to third parties at RSU Budi Rahayu is based on the existence of 5 SOPs for releasing medical record information with the procedure for the applicant to come with a power of attorney signed by the patient and the patient's identity requirements, and if the request is from the police it must be with a police letter. directly or from the director's letter. Data creation for the release of medical record documents takes 2-3 days. In the data creation process, sometimes there are inhibiting factors when the doctor responsible for the patient is not in the room and the files needed to release the information are sometimes not found. The conclusion obtained from this research is that the release of medical record information to third parties at RSU Budi Rahayu is in accordance with theory even though there are still missing requirements and obstacles related to doctors not being in place and files for data release not being found.